Polyproline II helical structure in protein unfolded states: Lysine peptides revisited - Rucker, Adam L. (Cold Spring Harbor Laboratory Press, 2002)
The left-handed polyproline II (PPII) helix gives rise to a circular dichroism spectrum that is remarkably similar to that of unfolded proteins. This similarity has been used as the basis for the hypothesis that unfolded proteins possess considerable PPII helical content. It has long been known that homopolymers of lysine adopt the PPII helical conformation at neutral pH, presumably a result of electrostatic repulsion between side chains. It is shown here that a seven-residue lysine peptide also adopts the PPII conformation. In contrast with homopolymers of lysine, this short peptide is shown to retain PPII helical character under conditions in which side-chain charges are heavily screened or even neutralized. The most plausible explanation for these observations is that the peptide backbone favors the PPII conformation to maximize favorable interactions with solvent. These data are evidence that unfolded proteins do indeed possess PPII content, indicating that the ensemble of unfolded states is significantly smaller than is commonly assumed.